The effect of the time on the antioxidant activity of three main vegetables - Mendes Ribeiro, Mariana (2018)
Introduction: Antioxidants are gathering increased attention. They are believed to play a key role in maintaining health with several studies demonstrating proportionality between the daily intake of foods rich in antioxidants and the decrease in the incidence of certain pathologies. Objective: It is known that vegetables are important sources of various antioxidant compounds. For the purpose of this study have been chosen three vegetables commonly used in Portugal - broccoli, spinach and watercress - to test the loss of antioxidant activity by the freezing process, with the aim of better understanding the actual amount of antioxidants that reaches the consumer when opts to frozen vegetables. Methodology: The samples were analysed according to two different methods - TPC and DPPH∙. The analyses were carried out in three different times: as fresh samples at day one, and after being freeze at third and sixth day. Main findings: IC50 value ranged from 11.91 mg/ml (broccoli) to 6.71 (watercress) mg/ml and TPC content ranged from 1.18 mg eq. gallic acid/ g sample (broccoli) to 2.07 mg eq. gallic acid/ g sample in the first day. The higher antioxidant activity was observed at the sixth day of frozen for spinach and watercress, and the highest phenol content was detected on the 3rd day for all the vegetables studied. Conclusions: Our studies are in line with literature, reporting that phenolic contents in vegetables remains unchanged or increase during freezing processes. More studies are needed to understand the mechanism involve in this processes. However, these properties can open doors to innovation in the food industry. Ongoing studies are being performed in this sense.